The Emergence of Global Maritime Fulcrum Indonesia's Maritime Strategy and its Linkage with U.S Indo-Pacific Strategy and China-Belt and Road Initiative - Andi Purwono (JPW (Jurnal Politik Walisongo), 2025)
The purpose of this paper is to understand the concept and factors behind the emergence of Indonesia's maritime strategic vision, known as the Global Maritime Fulcrum. A vision of Indonesia's maritime strategy was presented by President Joko Widodo in 2014. The emergence of the Global Maritime Fulcrum is inextricably linked to ideas, values, and norms believed to originate from Indonesia itself, as well as external influencing factors such as Indonesia's views on changes and shifts in international political dynamics in the Indo-Pacific region namely the rivalry between the United States with the Indo-Pacific Strategy and China with the belt and road initiative. The ability to recognize identity in a strategic geographical location as a maritime island state is one of the internal factors that also influenced the emergence of this idea. Other factors that also support the influence of GMF ideas include the changes in the geopolitical dynamics of the Indo-Pacific region over the last decade since the emergence of China’s strategy through the Belt and Road Initiative in 2013 it has made the situation in the Indo-Pacific region even more interesting for study. The dominance of the presence of the United States and its allies, such as Japan, India and Australia in the Indo-Pacific region began to be disrupted by the presence of China under the Belt and Road Initiative programs. Indonesia, as a country with a strategic geographical location in the Indo-Pacific region, is in the middle of the rivalry between the two major powers of the United States and China. Indonesia must recognize and keep an eye on the changing geographical and political security situation in the Indo-Pacific. The Global Maritime Fulcrum, which emerged in 2014, is the right place to know where and how Indonesia is positioned to respond.